Procedural Success and Safety of Cryoablation Versus Radiofrequency Ablation in Atrioventricular Nodal Reentrant Tachycardia: A Systematic Review and Meta-Analysis - Putri, Evira Agustina; Tunisa, Izza; Suciati, Putri Ayu (Medicinus, 2024)
Background: This meta-analysis compares cryoablation and radiofrequency ablation efficacy, safety, and procedural outcomes in atrioventricular nodal reentrant tachycardia (AVNRT). This meta-analysis aims to compare procedural success, long-term recurrence, and complication rates of cryoablation versus radiofrequency ablation in the treatment of AVNRT. Methods: Following PRISMA 2020, PubMed, EMBASE, and Scopus were searched (25 September 2025). Eligible randomized or observational studies directly compared CRYO versus RFA for AVNRT and reported procedural success, recurrence, and/or complications. Risk of bias was assessed (ROBINS-I for non-randomized studies). Pooled effects were calculated in RevMan 5.4 using random-effects models; risk ratios (RR) were used for dichotomous outcomes and standardized mean differences (SMD) for continuous outcomes. Estimates used the Wald-type method with REML; heterogeneity was summarized with I². Result: Sixteen studies were included. Acute procedural success was equivalent between CRYO and RFA (RR 1.00, 95% CI 0.99–1.02; p=0.47; I²=0%). CRYO showed higher recurrence during follow-up (RR 2.29, 95% CI 1.49–3.53; p=0.0002; I²=39%). Complications favored CRYO (RR 0.51, 95% CI 0.28–0.92; p=0.03; I²=0%). Fluoroscopy time was shorter with CRYO (SMD −0.42, 95% CI −0.66 to −0.19; p=0.0004; I²=87%), while overall procedure duration was similar (SMD 0.12, 95% CI −0.06 to 0.31; p=0.19; I²=79%). Overall risk of bias was predominantly low. Conclusions: CRYO and RFA achieve comparable acute success in AVNRT. CRYO confers fewer complications and lower fluoroscopy exposure but a higher recurrence risk, highlighting a safety–durability trade-off.